Nutritional and physical activity status among adults living in low-cost housing area in Selangor - Razinah Sharif,; Lim, Siew Wen; Roslee Rajikan, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study aimed to assess the nutritional and physical activity status among adults living in low-cost housing area. This cross-sectional study involved 115 adults aged from 18 to 59 years old (46 male and 69 female). Anthropometric and body composition measurements of height, weight, body fat percentage, waist and hip circumference were taken. Biochemical measurements included blood glucose, blood cholesterol and blood pressure. Dietary intake was evaluated by interviewing subjects using Food Frequency Questionnaires (FFQ). Physical activity status was determined by interviewing subjects using International Physical Activity Questionnaire (IPAQ). Most of the subjects were found to be mainly on low socioeconomic status and working as blue collar workers. The mean body mass index (BMI) for men and women were 27.3 ± 6.3 kg/m2 and 28.5 ± 5.3 kg/m2, respectively. The waist-hip ratio of men and women were 0.92 ± 0.07 and 0.86 ± 0.06, respectively. Mean blood pressure observed was 128.8 ± 18.8 mmHg (systolic) and 78.2 ± 12.1 mmHg (diastolic). Mean blood glucose was reported to be 6.6 ± 3.2 mmol/L while the mean blood cholesterol was 5.2 ± 1.0 mmol/L. Overall energy intake was 2705 ± 603 kcal with the contribution of 53.4% carbohydrate, 13.5% protein and 32.5% fat to overall energy intake. The nutrients that did not achieve Malaysia’s Recommended Nutrient Intake (RNI) were calcium (73.1%), thiamine (70.5%), folate (25.0%) and vitamin A (19.6%). The mean physical activity of subjects was 6739.8 ± 8135.6 MET-min/week (high physical activity). In conclusion, the adults living in low-cost housing have unsatisfactory nutritional status yet they have good physical activity level which might be contributed by their occupation.